A comparative study between emergency department provisional diagnoses and final discharge diagnoses in tertiary and quaternary health centers of India (Panacea Journal of Medical Sciences, 2022)
Background: An Emergency Department (ED), or the Emergency Room (ER), is a specialized patient care facility in tertiary and quaternary health care centers dedicated to Emergency Medicine. The main function of which, is to take care of patients with immediate and emergent health issues. In view of limited literature on Emergency Medicine in India, a comparative study of the admission and discharge diagnoses was performed, as a baseline for future reference in continuous quality improvement.Aim: A scientific endeavor dedicated to undertake a comparative study between the emergency department provisional diagnosis and the final inpatient discharge diagnosis, thus determining the diagnostic accuracy of the emergency medicine department in large health care centers of India.Material and Methods: A total of 3000 patients visiting the emergency department were considered and a comparative study was performed between the emergency department diagnoses and the final discharge diagnoses of these patients after admission to respective specialties.Result: In 81% cases the emergency department diagnoses was found to be concordant with the discharge diagnoses of the patients under study, and the concordance was found to be statistically significant.Conclusion: According to our study, the initial diagnoses made by emergency department physicians were mostly consistent with the final diagnoses. The significance of a correct diagnosis in the emergency department is far reaching. A correct diagnosis of the disease in the emergency enables prompt implementation of desired management protocols facilitating better patient outcomes and favorable disease prognosis. However, our study also highlights the need for further improvement in the diagnostic protocols in the emergency department.